Tectonic Control of a Change in Sedimentary Environment at 10 Ma in the Northeastern Tibetan Plateau. Issue 14 (15th July 2018) - Zhang, Tao; Han, Wenxia; Fang, Xiaomin; Miao, Yunfa; Zhang, Weilin; Song, Chunhui; Wang, Yadong; Khatri, Dhan Bahadur; Zhang, Zhigao
Abstract: Tectonic uplift and climate change play a key role in the evolution of sedimentary systems in terrestrial basins. The Qaidam Basin in the northeastern Tibetan Plateau is well suited for studying these processes because of its location and its thick, continuous sequence of Cenozoic sediments. Unfortunately, however, there is a lack of continuous, well‐dated sedimentary records from the region. In the present study, we combined grain‐size analyses of sediment cores and outcrop samples with structural analysis of seismostratigraphic data from the western Qaidam Basin. The results reveal dramatic shifts in the depositional environment at 11.5–10 Ma, coeval with the topographic development of the area. Together with paleoclimatic analysis and a conceptual model, we conclude that tectonic movements, rather than climatic changes, were the dominant forcing factor. Plain Language Summary: The interaction of climate and tectonics is believed to be a key controlling factor on Earth surface processes. However, it is still an open question to distinguish who provides the first driving force for those processes. The evidences based on the sedimentological and seismological study from the western Qaidam Basin suggest that a significant shift of sedimentation environment took place at 10 Ma, which is coeval with the development of structural landform but out of phase with climate change here. We therefore pointed out that tectonic activities rather than climate change controlled the sedimentary environment change at 10 Ma in the northeastern Tibetan Plateau, providing a new insight for understanding impacts of Tibetan Plateau uplift on Earth surface evolution during the late Cenozoic. Key Points: Middle Miocene‐Pliocene sedimentary records were obtained from the northeastern Tibetan Plateau A significant change in depositional environment occurred at 10 Ma Seismostratigraphic and paleoclimatic analysis indicates that tectonic uplift was the main cause of the change at 10 Ma